2007
DOI: 10.1007/s00415-006-0332-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of interferon beta in multiple sclerosis patients with or without serum neutralizing antibodies

Abstract: To analyze the in vivo biological effect of anti-interferon beta (IFN-beta) neutralizing antibodies (NABs), blood concentrations of neopterin, beta2microglobulin (Beta2-MG), mRNA-dependent myxovirusresistant protein A (MxA) and dsRNA-dependent protein kinase (PKR) were measured before (predose) and 24 hours after (postdose) IFN-beta administration in 49 patients with multiple sclerosis (MS) with (n = 25) and without (n = 24) NABs. The results indicated that predose levels of MxA-mRNA and PKR-mRNA were highly v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…[4][5][6] Myxovirus resistance protein A (MxA) has been used as a biomarker of IFN␤ response in patients with MS. [7][8][9] Viperin and interferoninduced protein with tetratricopeptide repeats 1 (IFIT-1) are, like MxA, specifically and highly induced by IFN␤. 1-3 IFN␤ binds to the IFN␣/␤ receptor (IFNAR) to exert its biologic effects, including induction of antiviral proteins and up-and down-regulation of immune-regulatory genes.…”
mentioning
confidence: 99%
“…[4][5][6] Myxovirus resistance protein A (MxA) has been used as a biomarker of IFN␤ response in patients with MS. [7][8][9] Viperin and interferoninduced protein with tetratricopeptide repeats 1 (IFIT-1) are, like MxA, specifically and highly induced by IFN␤. 1-3 IFN␤ binds to the IFN␣/␤ receptor (IFNAR) to exert its biologic effects, including induction of antiviral proteins and up-and down-regulation of immune-regulatory genes.…”
mentioning
confidence: 99%
“…Other studies reported a fall in serum neopterin levels or in the levels of other IFN biologic response markers, including matrix metalloproteinases (MMPs), beta2 microglobulin, MxA, viperin, TNF-related apoptosis-inducing ligand (TRAIL) and X-linked inhibitor apoptosis factor-1 (XAF-1), when NAb titers were elevated in patients with MS [6,20,38-41]. Data clearly support the hypothesis that neopterin is a sensitive measure of biological response to IFNβ and is reduced by the presence of NAbs.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of IFNβ to its cell-surface receptor stimulates several immunological processes, including neopterin [D- erythro -6-(1',2',3'-trihydroxypropyl)-pterin] production [6] and trp degradation [7,8]. In vitro evidence demonstrated that both IFNβ and IFNγ induce neopterin production [9] and activate the enzyme indoleamine (2,3)-dioxygenase (IDO).…”
Section: Introductionmentioning
confidence: 99%
“…After binding of IFNb to the type I IFN receptor, a signaling cascade is induced resulting in the expression of various genes [75]. Some of these gene products are 2¢,5¢-oligoadenylate (2-5A) synthetase [76,77], neopterin [78][79][80][81], b2-microglobulin [78,79,81] and myxovirus protein A (MxA) [76,77,[81][82][83], the latter is well established as IFNb bioactivity marker [84].…”
Section: Correlation Between Pharmacokinetic and Pharmacodynamic Markersmentioning
confidence: 99%